Psychometric Evaluation of the Italian Obsessive Compulsive Inventory–Child Version: Factor Structure and Predictive Validity at One-Year Follow-Up in Adolescents. (2nd October 2019) - Pozza, Andrea; Barcaccia, Barbara; Dèttore, Davide
Abstract: Obsessive–compulsive disorder (OCD) in adolescents is understudied in Italy. This study evaluated the Italian Obsessive Compulsive Inventory–Child Version (OCI–CV) and its predictive validity on OCD symptoms at 1-year-follow-up, an aspect that was not investigated by previous international research. Use of OCI–CV in schools might enhance early identification of OCD symptoms.